POWER KEPEMIMPINAN: STUDI PADA PLAZA PELAYANAN PUBLIK KABUPATEN BELU - Yohanes Kornelius Ethelbert; Indryati Indryati; Bernardus Donggo Raga (Journal of Education on Social Science (JESS), 2026)
Abstract The traditional perspective on power as a control function is no longer the best strategy for improving employee performance. Power relations within organizations must be examined through a different approach. This paper will examine a new model for understanding power relations through three main dimensions: situational power, relational power, and dynamic power. This study aims to examine the dynamics of leadership power in public service products at the Public Service Plaza Office in Belu Regency, Dinas Penanaman Modal dan Pelayanan Terpadu Satu Pintu (DPMPTSP) East Nusa Tenggara Province, Indonesia. This study uses a qualitative approach aimed at exploring the views, experiences, and feelings of informants about leadership power. In addition to in-depth interviews and Focus Group Discussions (FGDs), the researcher also conducted a literature review to obtain more complete and comprehensive data. The results show that the quality of public service is considered successful because leaders play a role in improving the quality of employee work to achieve organizational goals. This role is seen from their ability to manage power in a balanced manner based on three elements: situational power, relational power, and dynamic power.